Plasma homocysteine levels are positively associated with interstitial lung disease in dermatomyositis patients with anti‐aminoacyl‐tRNA synthetase antibody. Issue 1 (6th September 2020) - Sekiguchi, Akiko; Endo, Yukie; Yamazaki, Sahori; Uchiyama, Akihiko; Shimizu, Akira; Motegi, Sei‐ichiro
Abstract: Homocysteine is a sulfhydryl‐containing amino acid that is derived from dietary methionine, and there has been increasing evidence that elevated plasma homocysteine levels are associated with increased risk of central and peripheral vascular disorders, including carotid, coronary and peripheral arterial diseases, and Raynaud's phenomenon. Recently, associations of plasma homocysteine levels with autoimmune diseases such as systemic lupus erythematodes and systemic sclerosis have been reported. However, no study analyzed the association between plasma homocysteine levels and dermatomyositis (DM). The objective of this study was to examine plasma homocysteine levels and their clinical associations in patients with DM. Plasma homocysteine levels in 28 Japanese patients with DM and 22 healthy controls were examined. We found that the plasma homocysteine levels in DM patients were significantly higher than those in healthy individuals (15.8 ± 1.1 vs 8.5 ± 0.5 µmol/L, P  < 0.01). Presence of mechanic's hand, complication of interstitial lung disease (ILD), high serum Krebs von den Lungen‐6 (KL‐6), surfactant protein‐D and creatine kinase levels, and anti‐aminoacyl‐tRNA synthetase (ARS) antibody (Ab) positivity were significantly more prevalent among DM patients with elevated plasma homocysteine levels. The plasma homocysteine levels in DM patients with mechanic's hand, ILD and anti‐ARS Ab were significantly higher than those in DM without those features. Furthermore, the plasma homocysteine levels were positively correlated with serum KL‐6 levels. These results suggest that the pathogenesis of elevated plasma homocysteine levels may be associated with ILD in DM patients, especially with anti‐ARS Ab, and further examination is required.